Usage intentions, attitudes, and behaviors towards energy-efficient applications during the COVID-19 pandemic - Pop, Rebeka-Anna; Dabija, Dan-Cristian; Pelău, Corina; Dinu, Vasile (Journal of Business Economics and Management, 2022)
Energy waste is an emerging issue worldwide, with energy conservation goals, such as conscious energy consumption, playing a crucial role in helping the environment. The rapid growth of smart appliances has led to the development of mobile applications, with an increased interest among policymakers to design eco-saving plans for optimizing power and battery consumption.  This study aims to explore the usage intention of energy-efficient applications, through young consumers’ energy conservation behavior, behavioral characteristics, and COVID-19 pandemic experience. Based on empirical investigation, a survey was applied in Romania among 590 mobile app users. The data were tested using partial least square structural equation modeling (SmartPLS, version 3). The results indicate the impact of behavioral characteristics, namely, energy conservation attitude, subjective norms, and environmental knowledge on young users’ energy conservation behavior. The influential effect of COVID-19 on energy-saving behavior was also proven. Energy conservation behavior, and functional and hedonic values positively influence Millennials’ and Gen Zers’ energy-efficient app usage intentions. The study also discusses some implications for policymakers, marketers, and software developers, as well as providing theoretical suggestions for future work.